Quantification of the Radiopacity of Onyx during Embolization - Yuan Yuan Jiang; Ye-eun Jo; Jung Min Woo; Ok Kyun Lim; Changmo Hwang; Jun Young Maeng; Jieun Kim; Namkug Kim; Deok Hee Lee (Neurointervention, 2017)
PurposeOnyx has been successfully applied in the treatment of various neurovascular lesions. However, some experience is required to get accustomed to its unpredictable fluoroscopic visibility during injection. This in vitro study aimed to evaluate the characteristics of radiopacity change in a simulated embolization procedure.Materials and MethodsUsing a bench-top Onyx injection experiment simulating a typical brain arteriovenous malformation embolization, nine cycles of casting modes (continuous injection) and plugging modes (injection with intermittent pauses) were performed. Radiodensity of Onyx droplets collected from the microcatheter tip and the distal head portion of the microcatheter were measured as time lapsed. Distribution of droplet radiodensity (radiodensity) and distribution of radiographic grade (grade) were analyzed and compared by repeated measurements.ResultsWithin-group analysis revealed no significant radiodensity change with time (P>0.05). The radiodensity was significantly higher in the casting mode than in the plugging mode (P<0.01). The lateral radiograph of the microcatheter showed higher radiopacity (P<0.01) and better evenness (P<0.01) in the casting mode than in the plugging mode. A significant difference in microcatheter attenuation (both radiographic grade mean and SD; P<0.01) was noted between the two modes. Radiodensity had a significant influence on the radiopacity and radiopacity evenness of the microcatheter.ConclusionThe radiopacity of the Onyx can vary significantly over time because of early precipitation of tantalum powder. Radiopacity decreased significantly during plugging modes, characterized by pauses between injections.